Pengaruh Konsentrasi Ragi Tape (Saccharomyces Cerevisiae) terhadap Kadar Bioetanol Pada Proses Fermentasi Biji Alpukat (Persea Americana Mill) - Rizwan, Mohd.; Diah, Anang Wahid M.; Ratman, Ratman (Jurnal Akademika Kimia, 2018)
Avocado seed contains high level of starch and it can be used as one of the raw materials for bioethanol. This study aimed to determine the influence of variation concentration of tape starter toward bioethanol level in the fermentation process of avocado (persea americana Mill.) seed. Some process on this research were delignification with 4% NaOH, hydrolysis with 12% HCl, and fermentation with various concentrations of yeast tape (saccharomyces cerevisiae) ie 10%, 20% and 30% of substrate volume for 5 days. Bioethanol level was determined by using alcoholmeter. The highest bioethanol level was obtained in the addition of yeast tape as much as 30% of substrate that was an equal to 32.65% with density of 1.0029 g/mL.